Effects of sugar alcohols as water activity reducing agents on the secondary metabolism of local fungi - Mohd Fauzi, Nur Aziemah (2016)
Fungi have become a natural product for drug discovery. Growing a fungus in different media would lead to the alteration in secondary metabolites profile. The fungi used for this project are Aspergillus longivesica (SHSF), SHSC9, Trichoderma virens (FID5Cl) and Talaromyces aculateus (F23D25Cl). All of these fungi is local fungi which live in high humidity environment. The use of sugar alcohols to reduce the water activity can induce stress to the fungi. Thus, alter the secondary metabolite profile. In order to achieving this, the fungus was inoculate in 24 different combination and concentration of sugar alcohol. After undergoing freeze drying and extraction, the UHPLC analysis was carried out. Qualitative and quantitative analysis of 96 chromatogram was carried out. The use of sugar alcohols as water activity reducing agent was alter the secondary metabolites profile of each fungi. However, the effect of each sugar alcohols are different to different fungi.